2019
DOI: 10.1016/j.neuroimage.2018.10.044
|View full text |Cite
|
Sign up to set email alerts
|

Modulating functional connectivity with non-invasive brain stimulation for the investigation and alleviation of age-associated declines in response inhibition: A narrative review

Abstract: with non-invasive brain stimulation for the investigation and alleviation of age-associated declines in response inhibition: A narrative review,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 214 publications
(305 reference statements)
1
15
0
Order By: Relevance
“…There are other techniques, such as measures of glucose utilization [257], beta-amyloid burden [258], synaptic density [259], optical imaging [260], PET markers of neuroinflammation [261,262], MR spectroscopic measures of the neurotransmitters [263,264] and even non-invasive brain stimulation [265,266] that may further help understand the basis of BOLD signals, but are beyond the scope of this review.…”
Section: (B) Neuronal Integrationmentioning
confidence: 99%
“…There are other techniques, such as measures of glucose utilization [257], beta-amyloid burden [258], synaptic density [259], optical imaging [260], PET markers of neuroinflammation [261,262], MR spectroscopic measures of the neurotransmitters [263,264] and even non-invasive brain stimulation [265,266] that may further help understand the basis of BOLD signals, but are beyond the scope of this review.…”
Section: (B) Neuronal Integrationmentioning
confidence: 99%
“…The pre-supplementary motor area (pre-SMA), which is a node of the MD network [4,6], has been reported to be involved in the imitation inhibition task [15,16], as well as in the initiation of movement, alteration of movement plans, and response inhibition [17]. Moreover, numerous studies have shown that anodal stimulation of the pre-SMA enhances the performance of cognitive tasks, including response inhibition [18]. This tDCS study aimed to investigate individual differences in the involvement of the MD network in imitation inhibition according to autism spectrum traits.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research shows neurophysiological, structural and functional changes occurring in the aging brain that lead to a decline in cognitive 17 and motor functions [18][19][20][21][22] ; for review, please refer to 23,24 . As such, motor skill acquisition is typically diminished in older adults 3,25,26 .…”
Section: Introductionmentioning
confidence: 99%